2016
DOI: 10.4142/jvs.2016.17.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gonadotropin-releasing hormone administration or a controlled internal drug-releasing insert after timed artificial insemination on pregnancy rates of dairy cows

Abstract: This study investigated the effects of gonadotrophin-releasing hormone (GnRH) administration (Experiment 1) and a controlled internal drug-releasing (CIDR) insert (Experiment 2) after timed artificial insemination (TAI) on the pregnancy rates of dairy cows. In Experiment 1, 569 dairy cows that underwent TAI (day 0) following short-term synchronization with prostaglandin F2α were randomly allocated into two groups: no further treatment (control, n = 307) or injection of 100 µg of gonadorelin on day 5 (GnRH, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The AI number may affect CR; differences in CR between AI number groups have been reported in zebu cattle (Mollah, Gofur, Asaduzzaman, & Bhuiyan, ). In addition, other factors have been associated with CR in other beef cattle breeds and in dairy cattle, these include the following: age of heifers at first AI, parity, interval from calving to first AI, and AI season (Jeong, Choi, Kang, Hur, & Kim, ; Kruif, ; Kuhn, Hutchison, & Wiggans, ; Maufti, Alam, Sarker, Bostami, & Das, ; Sharifuzzaman, Barman, Matin, Rokonuzzaman, & Ashadul, ; Shiddiqui et al., ). Yet, there have been no studies investigating the effects of interactions between AI number and these other factors on CR in Japanese Black cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The AI number may affect CR; differences in CR between AI number groups have been reported in zebu cattle (Mollah, Gofur, Asaduzzaman, & Bhuiyan, ). In addition, other factors have been associated with CR in other beef cattle breeds and in dairy cattle, these include the following: age of heifers at first AI, parity, interval from calving to first AI, and AI season (Jeong, Choi, Kang, Hur, & Kim, ; Kruif, ; Kuhn, Hutchison, & Wiggans, ; Maufti, Alam, Sarker, Bostami, & Das, ; Sharifuzzaman, Barman, Matin, Rokonuzzaman, & Ashadul, ; Shiddiqui et al., ). Yet, there have been no studies investigating the effects of interactions between AI number and these other factors on CR in Japanese Black cattle.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study ( Jeong et al, 2016) revealed that GnRH administration after 5 days of timed AI in dairy cows resulted in the ovulation of a dominant follicle (DF) and formation of an accessory CL. Similar results were observed with the administration of hCG on Day 5 in cows (Schmitt et al, 1996a;Hanlon et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Khoramian et al (2011), hCG and controlled internal drug release (CIDR) applications after AI in repeat breeder cows led to higher conception rates. Application of CIDR following AI between days 5-12 (Hokmabad et al 2012), days 5-9 (Ghasemzadeh-Nava et al 2007) and days 3.5-18 (Jeong et al 2016) was reported to be successful in increasing the conception rate. Garcia-Ispierto and López-Gatius (2017) reported that progesterone supplementation either early (3-5 days) or late (15-17 days) in the cycle increased the conception rate.…”
Section: Discussionmentioning
confidence: 99%
“…In these hormonal applications following AI, there may be differences between the rates of conception (Yan et al 2016). Some studies have reported that progesterone supplementation (Ghasemzadeh-Nava et al 2007;Jeong et al 2016;Parr et al 2017) and hCG administration (Kendall et al 2009;Khoramian et al 2011;Sánchez et al 2018) increase the pregnancy rate, while some studies (Shams-Esfandabadi and Shirazi 2007; Ergene 2012) have reported no effect. Yan et al (2016) reported that the benefit of progesterone supplementation on fertility of cows required exogenous progesterone supplementation to start between Day 3 to 7.…”
mentioning
confidence: 99%